Entre clérigos anda el juego. La versión griega de los Martialis distieha del deán Martí y el Lusus convivialis de Interián de Ayala - Gil, Luis (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 1991)
In Eook VI of Manuel Marti’s latin Epistolary, which includes bis correspondence with Juan Interián dc Ayala, published by 6. Mayáns (Madrid, 1736) and reprinted by P. Wesseling (Amsterdam, 1738), appear 28 epigrams by Martial transíated into the Greek. Scbolars of dic 1 Sth eentury kncw that Mayáns had in his possession sorne versions which did not see ihe light of day. lhe aforemnentioned versions, togetber with ihose that were published. appear on pages 11-118 of ms. 6364 frorn ihe Serrano Morales Collection in Valencia Publie Library. Ibis ve-as precisely the Mar/mían original subniitted for printing in which these versions were propcrly crossed out. They total 14 poems whose publication was probably thought olfensive to the readers’ sensitivity hecause of their salaciousness. 3he fact that a priest should oecupy bis leisure in such improper activities lér sacerdotal solemnity and, in addition, should send diese garnes of bis wit to a triar, professor of J-lebrew in Salamanca. comnpelling ¡Pm to write Lusus Convivia/is, is an aínusing piece of evidence of tIme abyss thai existed between the real Spain and tbe offieial Spain in the bcginning of the 1 Sth ccntury. Itence, the interest of these medí/a Martin,ana.